Transcriptional responses to long-term salinity stress and acclimation in Mytilus galloprovincialis from Bosphorus - İçağasıoğlu, Elif. (Thesis (Ph.D.) - Bogazici University. Institute of Environmental Sciences, 2021., 2021)
Mytilus galloprovincialis is an ideal model organism for studying adaptation, as it can inhabit highly variable environments. We examined its acclimation to chronic and gradual long-term salinity stress. Gene expression, pathway and gene set enrichment analyzes were used with RNA-Seq with de novo transcriptome. In our results, low salinity was observed to be correlated with high energy expenditure. Cholinergic ciliary stimulation and calcium signalling were involved. Volume regulation was enhanced by nitrogen metabolism and alterations of membrane permeability. Arachidonic acid metabolism and Na+/K+ pump were inversely regulated with salinity in this context. Genes involved in the synthesis of serine, proline, glycine, ornithine and betaine were also regulated. Protein turnover and nucleotide metabolism were also inversely regulated with salinity. In addition to these regulations, some of the observed metabolic regulations are associated with cancereous cells, as well. Parallel to energy requirement, aerobic and anaerobic respiration genes were parallely regulated, as well as genes of reciprocally regulated processes of glycolysis and gluconeogenesis. Although there are many types/causes of cancer, there are common adaptations that support survival and proliferation, such as apoptosis suppression and the aforementioned metabolic regulations. In addition, in our study, parallel with these metabolic regulations, p53 and p63 originated apoptosis were triggered with participation of TP53 apoptosis effector (PERP), TLRs and TNFSF14. Understanding genes and pathways that triggers apoptosis in this context in our study, and investigating their projections in humans, may be important in our understanding of cancer and in developing therapeutic and protective products such as vaccines.
Keywords: Salinity -- Bosphorus.